Who were the Babylonians? - Arnold, Bill T. (Archaeology and biblical studies ;, 2004)
Who was Hammurapi, and what role did his famous "law code" serve in ancient Babylonian society? Who was the mysterious Merodach-baladan, and why did the appearance of his emissaries in Jerusalem so upset Isaiah? Who was Nebuchadnezzar II, and why did he tear down the Solomonic temple and drag the people of God into exile? In short, who were the Babylonians? This engaging and informative introduction to the best of current scholarship on the Babylonians and their role in biblical history answers these and other significant questions. The Babylonians were important not only because of their many historical contacts with ancient Israel but because they and their predecessors, the Sumerians, established the philosophical and social infrastructure for most of Western Asia for nearly two millennia. Beginning and advanced students as well as biblical scholars and interested nonspecialists will read this introduction to the history and culture of the Babylonians with interest and profit. - Publisher